2015
DOI: 10.1093/heapro/dav081
|View full text |Cite
|
Sign up to set email alerts
|

Young adults: beloved by food and drink marketers and forgotten by public health?: Fig. 1:

Abstract: Young adults are a highly desirable target population for energy-dense, nutrient-poor (EDNP) food and beverage marketing. But little research, resources, advocacy and policy action have been directed at this age group, despite the fact that young adults are gaining weight faster than previous generations and other population groups. Factors such as identity development and shifting interpersonal influences differentiate young adulthood from other life stages and influence the adoption of both healthy and unhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 29 publications
1
87
0
1
Order By: Relevance
“…This study contributes to the literature on food, beverage, and snack marketing in several ways. Other social media research studies have included a smaller subset of brands, fewer social media platforms, or provided a narrative review of evidence or broad commentaries on public health concerns related to social media advertising . Our findings are the first to evaluate growth of brands' social media accounts over a 9‐year period and capture the variety of advertising practices companies used on five platforms over a 1‐year period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study contributes to the literature on food, beverage, and snack marketing in several ways. Other social media research studies have included a smaller subset of brands, fewer social media platforms, or provided a narrative review of evidence or broad commentaries on public health concerns related to social media advertising . Our findings are the first to evaluate growth of brands' social media accounts over a 9‐year period and capture the variety of advertising practices companies used on five platforms over a 1‐year period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Food companies' use of social media accounts is newly emerging and relatively unexplored. A few studies have shown that Facebook pages that are managed by food companies promote unhealthy products and increase brand recognition among youth . But no studies have examined the landscape of social media food, beverage, and snack ads across multiple social media platforms over an extended period of time.…”
Section: Introductionmentioning
confidence: 99%
“…In light of unhealthy food and beverage brands heavily using social media advertising (Montgomery, Chester, Grier, & Dorfman, 2012), public health professionals have called for interventions and polices targeted at protecting children (World Health Organisation, 2010), adolescents (Williams, 2013) and young adults (Freeman, Kelly, Vandevijvere, & Baur, 2015). The predominantly voluntary nature of advertising codes meant to only limit young children's exposure to unhealthy food and beverage marketing has had a minimal impact on their actual exposure to advertising (BoelsenRobinson et al, 2015;Obesity Policy Coalition, 2011).…”
Section: Exposure To Food and Beverage Marketing On Social Mediamentioning
confidence: 99%
“…The rate of weight gain during the young adulthood period is the fastest across adulthood . A period in which creating an identity and learning cooking skills take place this group are particularly vulnerable to food industry marketing . Interventions designed by health professionals and social marketers can be problematic if they do not ‘connect’ with the target audience .…”
Section: Introductionmentioning
confidence: 99%
“…23 A period in which creating an identity and learning cooking skills take place 17 this group are particularly vulnerable to food industry marketing. 24 Interventions designed by health professionals and social marketers can be problematic if they do not 'connect' with the target audience. 25 Social marketing is the use of commercial marketing tools and techniques, such as segmentation and targeted marketing activities, to address social issues.…”
Section: Introductionmentioning
confidence: 99%